Ministerial Decree No. 329/2015 Regarding the Issue of the Financial and Administrative Regulations for the Employment and Care of the Irregular Labor (Seasonal Agricultural Workers, the Construction Workers and the Like) = قرار وزاري رقم 329 لسنة 2015 بشأن إصدار اللائحة المالية والإدارية لتشغيل ورعاية العمالة غير المنتظمة عمال الزراعة الموسيميين وعمال المقاولات ومن في حكمهم - Egypt; The middle east library for economic services, translator. (2025)
Ministry of manpower decree no. 329 of the year 2015 regarding the issue of the financial and administrative regulations for the employment and care of the irregular labor (seasonal agricultural workers, the construction workers and the like) -- part 1: definitions and general provisions – part 2: the advisory committee for local employment – part 3: responsibilities of the department of the employment and care of irregular labor at the directorate – part 4: monitoring the employment – part 5: the financial system قرار وزارى رقم 329 لسنة 2015 بشأن إصدار اللائحة المالية والإدارية لتغشيل ورعاية العمالة غير المنتظمة (عمال الزراعة الموسميين وعمال المقاولات ومن فى حكمهم) – الفصل الأول التعاريف والأحكام العامة – الفصل الثانى اللجنة الاستشارية للتشغيل المحلى – الفصل الثالث اختصاصات إدارة تشغيل ورعاية العمالة غير المنتظمة بالمديرية – الفصل الرابع متابعة التشغيل – الفصل الخامس النظام المالى